2009
DOI: 10.1016/j.juro.2009.03.076
|View full text |Cite
|
Sign up to set email alerts
|

Novel Invasive Orthotopic Bladder Cancer Model With High Cathepsin B Activity Resembling Human Bladder Cancer

Abstract: The new murine bladder model described resembles human bladder disease, making it a useful tool for studying the molecular mechanisms of tumor progression and metastasis, and assaying antimetastatic and anti-invasive agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 17 publications
4
47
0
Order By: Relevance
“…Orthotopic MB49 tumors were developed as described 18 . Next, 100µl saline solution or BCG (2mg/ml) were instilled into the bladder twice a week, for 20 days.…”
Section: Argentinamentioning
confidence: 99%
“…Orthotopic MB49 tumors were developed as described 18 . Next, 100µl saline solution or BCG (2mg/ml) were instilled into the bladder twice a week, for 20 days.…”
Section: Argentinamentioning
confidence: 99%
“…23 Living organisms of an attenuated Mycobacterium tuberculosis bovis strain (Pasteur 1172 P2 strain) (Instituto Nacional de Producción de Biologicos, Buenos Aires, Argentina) containing 3 ϫ 10 6 cfu/mg were used.…”
Section: Bladder Tumor Cell Lines and Bcgmentioning
confidence: 99%
“…Thus, we evaluated the expression of iNOS and PPAR␥, and their biological relationship with tumor progression in a recently developed mouse bladder cancer model with different stages of invasion. 23 To clinically validate our murine model we also analyzed protein expression in human bladder tumors.…”
mentioning
confidence: 99%
“…Human tumors can be formed by different cell subpopulations with varying ability to metastasize and susceptibility to treatment, depending on the site of inoculation (Fidler, 1986). It has been observed that subcutaneous inoculation of murine MB49 bladder cancer cell lines induces lung metastases, and that inoculation of these cells in the bladder does not (Lodillinsky et al, 2009). Similar observations have been made for human tumors using 253J B-V cells .…”
Section: Heterotopic Tumor Growthmentioning
confidence: 99%
“…However, hematuria is the hallmark of tumor presence ( Figure 4B). Mice with 1x10 4 or 1x10 5 MB49 cell lines, inoculated by electrocautery, present hematuria about 15 or 9 days post-inoculation, respectively (Lodillinsky et al, 2009). Inoculation of 5x10 3 cells in the bladder previously treated with NO 3 Ag generates hematuria in all mice about 7 days after tumor implantation (Chade et al, 2008).…”
Section: Orthotopic Tumor Growthmentioning
confidence: 99%